Information Technology Governance Based On COBIT 4.1 Framework On PDAM Surabaya - Reza Oktorio Saputro; Erwin Sutomo; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2018)
PDAM Surabaya is the business unit belongs to an area that plays a crucial in fulfilling the needs of clean water communities that apply IT to assist in the achievement of the business objectives of the company. In its application, the maturity level of the IT management at PDAM Surabaya is the absence of supervision to run the procedure, so that the risk of many irregularities and discrepancies between operational processes that run with the policy that is set up. The solution to deal with these problems, the need for an IT governance is thus expected to produce maximum output to the company, help the decision-making process, as well as help the process of problem solving. As the basis for drafting of the COBIT framework is 4.1. External of it governance is a document that includes: 1) the alignment of the IT objectives with business goals that breakfast buffet by the 8 Primary and seven Secondary IT Process that supports the achievement of Strategic Aligment on Focus Area IT Governance. 2) Gap analysis in each domain, the results of processing the questionnaire found value is Defined as-is Process, while the results of the interviews found that the value of the to-be is Managed and Measurable. 3) stages the process increases as-is headed to-be each IT Process in order to produce the expected accomplishments. 4) Recommendations implementation of it governance based on COBIT 4.1 framework each IT Process so that relevant parties could easily carry out the monitoring of the management and measurement.